217 Why it is important to recognize Brugada syndrome in athletes: a case report. (8th December 2021) - Colangelo, Lidia; Colangelo, Maria; Stefanini, Luca
Abstract: Aims: The Brugada syndrome (Brs) is an inherited disorder associated with risk of ventricular fibrillation and sudden cardiac death in a structurally normal heart. The purpose of this case presentation was to spread awareness about this condition, highlight the importance of timely diagnosis and effective treatment of this channelopathy especially in asymptomatic young athletes at high risk of sudden cardiac death. Methods and results: In this report, we discuss the case of a 47-year-old male. He was a tennis player who performed a visit to the sports doctor to have issued a certificate for competitive fitness. He had no familiar history of sudden death or syncope. The patient's electrocardiogram (ECG) revealed J-point elevation and ST-segment elevation in the right precordial leads V1 and V2 positioned in the second, third, or fourth intercostal space, showing classic type II 'saddleback' morphology in V2 and BrS was suspected. Hence, the patient underwent Holter ECG monitoring with evidence of spontaneous type 1 Brugada pattern ('coved' morphology), as well as frequent ventricular ectopic beats with left branch block morphology. Indeed, a diagnosis of BrS was made. Antiarrhythmic prophylaxis therapy with hydroquinidine was initiated and the patient was suspended from competitive activity with a 3-month follow-up. Conclusions: The BrS is a hereditary disease characterized by a typical ECG pattern potentially predisposing active individuals with no patent structural heart disease to ventricular arrhythmias (VA) and sudden cardiac death (SCD). Nowadays, it is difficult to discern the true burden of BrS due to the unknown real prevalence of asymptomatic patients and the dynamic variability of the ECG pattern in individuals. The purpose of this case presentation was to spread awareness about this condition, highlight the importance of timely diagnosis, and effective treatment of this channelopathy especially in asymptomatic young athletes at high risk of SCD. Indeed, exercise may potentially worsen the ECG abnormalities in BrS patients, resulting in higher peak J-point amplitudes during the vasovagal reaction of the recovery period, possibly leading to an increased risk of cardiac events. Moreover, the enhanced vagal tone in athletes could be both a BrS risk factor and an exercise effect. For this reason, athletic pre-participation screening is essential for minimizing the risk for SCD in athletes participating in either competitive or leisure sporting activities.